Thar SHE Blows? Gender, Competition, and Bubbles in Experimental Asset Markets - Eckel, Catherine C.; Füllbrunn, Sascha C. (American Economic Review, 2015)
Do women and men behave differently in financial asset markets? Our results from an asset market experiment show a marked gender difference in producing speculative price bubbles. Mixed markets show intermediate values, and a meta-analysis of 35 markets from different studies confirms the inverse relationship between the magnitude of price bubbles and the frequency of female traders in the market. Women's price forecasts also are significantly lower, even in the first period. Implications for financial markets and experimental methodology are discussed. (JEL D14, D81, G01, G11, J16)